2023
DOI: 10.1097/inf.0000000000004080
|View full text |Cite
|
Sign up to set email alerts
|

Clinical Relevance of RSV and SARS-CoV-2 Coinfections in Infants and Young Children

Rosa Rodriguez-Fernandez,
Felipe González-Martínez,
Jimena Perez-Moreno
et al.

Abstract: We analyzed the frequency, clinical impact and severity of respiratory syncytial virus (RSV) and SARS-CoV-2 coinfections in a single pediatric center between March 2020 and January 2023. Compared to single RSV infections, RSV/SARS-CoV-2 coinfections were uncommon (2.1%), occurred more frequently during circulation of omicron, and were associated with increased disease severity as defined by longer hospitalization and increased need for high-flow nasal cannula.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(1 citation statement)
references
References 10 publications
(13 reference statements)
0
1
0
Order By: Relevance
“…A recent study revealed that co-infection with RSV enhances the severity of SARS-CoV-2 omicron infection in young children. These findings warrant detailed investigations into how RSV and SARS-CoV-2 co-infections impact the disease's outcome in children [48].…”
Section: Influenza and Sars-cov-2 Co-infection: Competition Or Sinist...mentioning
confidence: 90%
“…A recent study revealed that co-infection with RSV enhances the severity of SARS-CoV-2 omicron infection in young children. These findings warrant detailed investigations into how RSV and SARS-CoV-2 co-infections impact the disease's outcome in children [48].…”
Section: Influenza and Sars-cov-2 Co-infection: Competition Or Sinist...mentioning
confidence: 90%